Analisis Ketidakstabilan Performa Kerja Governor Mesin Diesel Penggerak Utama Pada Kapal MV Pekanbaru - A, Hanung Satria; Pujiyanto, Fajar; Wilastari, Santhi; Puryadi, Puryadi (Marine Science and Technology Journal, 2024)
The diesel engine is a vital component that serves as the ship's main propulsion system. This engine plays a crucial role in the efficiency and operational stability of the ship. One of the important parts of a diesel engine is the governor, which functions to regulate the engine's rotational speed to keep it stable. Problems with the governor can cause engine speed instability, leading to operational issues, reduced fuel efficiency, and a higher risk of damage. The study uses observational methods to identify the main causes of engine speed instability due to governor failure. Basic data include measurements and observations, maintenance history, and records of past failures. Observations on engine speed instability caused by governor failure focus on electrical issues, material wear, and extreme temperatures. This research emphasizes the importance of good and routine maintenance for the governor. Maintenance includes regular inspections, electrical maintenance, and the replacement of worn components. The research results are expected to provide practical recommendations for ship technicians to improve maintenance activities and address diesel engine speed instability issues. Implementing the findings of this research is expected to enhance the overall safety and operational efficiency of the ship